A new species of Bracon (Braconidae: Braconinae) from central Mexico, probable parasitoid of a weevil that feeds on roots of Argemone ochroleuca Sweet (Papaveraceae) - Rosa, Jaime Solis-De La; Martínez, Juan José; Benites, Pilar; Hernández-Cumplido, Johnattan; Zaldívar-Riverón, Alejandro (Zootaxa, 2023)
A new species of the braconine genus Bracon (subgenus Bracon), B. hidalguensis sp. nov., is described from the locality of Tasquillo in the state of Hidalgo, central Mexico. The new species was reared from roots of Argemone ochroleuca Sweet (Papaveraceae), where specimens of the weevil species Conotrachelus leucophaeus (Champion) (Curculionidae) were also obtained and thus probably it represents its host. The new Bracon species was characterised molecularly with DNA barcoding (COI) and a fragment of the variable D2–3 region of the nuclear ribosomal 28S gene.